2018
DOI: 10.1002/srin.201800371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cerium on the Behavior of Inclusions in H13 Steel

Abstract: The modification mechanism of cerium (Ce) on oxides and multilayer carbontrides in H13 steel is investigated by industrial trials and thermodynamic calculations. The morphology, composition, and size of inclusions are analyzed by scanning electron microscopy and energy dispersive spectroscopy. The main inclusions in H13 steel without Ce content in the molten steel are MgAl2O4 spinel inclusions and multilayer carbonitrides. The carbonitrides have a multilayer structure in which MgAl2O4 acts as the nucleation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
67
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 39 publications
2
67
1
Order By: Relevance
“…Rare earth elements present a remarkable efficacy in modifying inclusions and in facilitating purification and alloying of steel, given their unique electronic layer structure. This structure includes variable valence states, and the atomic size of the 4f layer is large, which creates absolute advantages in terms of mechanical properties and corrosion resistance of the slabs . Li Y et al conducted laboratory experiments to study the relationship between the Ce content (wt%: 0–0.0744) and the related properties; their work yielded 27Cr‐3.8Mo‐2Ni super FSS with superior microstructure, mechanical, and corrosion properties.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth elements present a remarkable efficacy in modifying inclusions and in facilitating purification and alloying of steel, given their unique electronic layer structure. This structure includes variable valence states, and the atomic size of the 4f layer is large, which creates absolute advantages in terms of mechanical properties and corrosion resistance of the slabs . Li Y et al conducted laboratory experiments to study the relationship between the Ce content (wt%: 0–0.0744) and the related properties; their work yielded 27Cr‐3.8Mo‐2Ni super FSS with superior microstructure, mechanical, and corrosion properties.…”
Section: Introductionmentioning
confidence: 99%
“…Lan et al found that the segregation ratios of alloying elements are decreased considerably after the addition of rare earth elements, and the grain boundary carbides are also inhibited. Huang et al discovered that the addition of elemental Ce effectively inhibits the heterogeneous nucleation of primary carbides in industrial H13 steel, and the number density of primary carbontrides is remarkably decreased with increasing Ce content. Li et al reported that the addition of elemental Mg in H13 steel converts Al 2 O 3 into MgAl 2 O 4 , and the MgAl 2 O 4 particle acts as a more effective heterogeneous nuclei and provides more nucleation sites than the Al 2 O 3 inclusion, resulting in a more uniform distribution of primary carbides .…”
Section: Introductionmentioning
confidence: 99%
“…13) It has been widely confirmed in the laboratory that the appropriate addition of rare earth content can significantly improve the impact toughness and toughness of materials. [14][15][16][17] Combined with the actual production process of H13 steel, it can be known that the H13 ingot will undergo high-temperature heating, forging and heat-treatment process. Therefore, dissolved by high temperature would be a more direct and effective way to reduce the detriment of the primary carbide.…”
mentioning
confidence: 99%